Urbanitat postnacional més enllà de l’estat (pluri)nacio(nal) en la UE: comparant Escòcia, Catalunya i el País Basc - Calzada, I (Institució Alfons el Magnànim, 2017)
This article compares three small, stateless, city-regional nation cases of Scotland, Catalonia, and the Basque Country after September 2014. Since the referendum on Scottish independence, depending on its unique context, each case has engaged differently in democratic and deliberative experimentation on the «right to decide» its future beyond its referential (pluri)nation(al)- states in the UK and Spain. Most recently, the Brexit referendum has triggered a deeper debate on how regional and political demands by these cases could re-scale the fixed (pluri)nation(al)-states’ structures while even directly advocating for some sort of «Europeanization». Based on a broader research programme on comparing city-regional cases titled «Benchmarking City-Regions», this paper argues that the differences in each of these three cases are noteworthy. Yet, even more substantial are their diverse means of accommodating smart devolutionary strategic pathways of self-determination through political innovation processes among pervasive metropolitanisation responses to a growing «post-national urbanity» pattern in the European Union. Thus, the paper examines: To what extent are the starting points of the levels of «smart devolution» for each case similar? What are the potential political scenarios for these cases as a result of the de- or recentralisation strategies of their referential (pluri)nation(al)-states? What are the most relevant distinct strategic political innovation processes in each case? Ultimately, this paper aims to benchmark how Scotland, Catalonia, and the Basque Country are strategically moving forward beyond their referential (pluri)nation(al)-states in such a new European geopolitical pattern we can call «post-national urbanity» by formulating devolution, and even independence, in unique metropolitan terms.